2022
DOI: 10.1186/s43161-022-00086-8
|View full text |Cite
|
Sign up to set email alerts
|

Effect of intradialytic exercises (IDE) on maximal oxygen consumption and quality of life undergoing hemodialysis in Indian population—a pilot study

Abstract: Background End stage renal disease (ESRD) is emerging as a major health issues across developing countries with limited access and awareness about the importance of exercises in daily life. People on prolong hemodialysis has difficulty in performing their activities of daily living (ADL). Loss of muscle mass is inevitable among patients on hemodialysis that leads to morbidity and mortality. Exercise is feasible during dialysis and can enhance quality of life. Increase in aerobic endurance by va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…Only the patients who fulfilled to complete more than 60% of HEP were included in the analysis. Fatigue is the most frequently described and globally recognized as a disabling symptom [15]; especially in CKD, fatigue is reported as one of the most common and debilitating symptoms [16]. Severe fatigue symptoms are reported in 25% of CKD patients, and approximately 70% report fatigue.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Only the patients who fulfilled to complete more than 60% of HEP were included in the analysis. Fatigue is the most frequently described and globally recognized as a disabling symptom [15]; especially in CKD, fatigue is reported as one of the most common and debilitating symptoms [16]. Severe fatigue symptoms are reported in 25% of CKD patients, and approximately 70% report fatigue.…”
Section: Discussionmentioning
confidence: 99%
“…There were no clinically significant differences between the IDE (EG) and control group at the end of 12 weeks period. There are no studies reported on IDE and FAS to support this, but a study conducted in India [16] evaluated the quality of life, peak oxygen consumption, and fatigue using the rate of perceived exertion (RPE) and showed a significant improvement after 12 weeks of IDE but had its limitations as it was single group study. The pathophysiology of fatigue in CKD is multifactorial.…”
Section: Discussionmentioning
confidence: 99%
“…Exercises are important since CKD patients have much lower levels of physical activity than healthy people. Additionally, the best predictor of death among ESRD patients has been noted to be low aerobic capacity, a biological fitness metric that can be increased by exercise (Grover et al, 2022).…”
Section: Significance Of the Studymentioning
confidence: 99%